2018
DOI: 10.1371/journal.pone.0192319
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Modified Tongxie Yaofang in diarrhea-predominant irritable bowel syndrome management: A meta-analysis of randomized, positive medicine-controlled trials

Abstract: ObjectiveTo systematically evaluate the efficacy and safety of Modified Tongxie Yaofang (M-TXYF) for the treatment of diarrhea-predominant irritable bowel syndrome (IBS-D).MethodElectronic databases including PubMed, Springer Link, EMBASE, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature (CBM), Wanfang, and Chinese Scientific Journals Database (VIP) were conducted from their inception through May 11, 2017 without language restrictions. Primary and secondary outcomes were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The Chinese herbal medicine Tongxie Yaofang was evaluated in a meta‐analysis of 23 randomised clinical studies in patients with IBS‐D (n = 1972) . Patients with IBS‐D receiving Tongxie Yaofang were significantly more likely to experience improvement of clinical symptoms vs other treatments (90.3% vs 72.7%, respectively; odds ratio, 4.0; 95% CI, 3.1‐5.3 [ie, pinaverium bromide alone or in combination with a probiotic or montmorillonite powder, glutamine, loperamide, miyarisan, or trimebutine maleate]) . The number needed to treat for Tongxie Yaofang was 5.7 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Chinese herbal medicine Tongxie Yaofang was evaluated in a meta‐analysis of 23 randomised clinical studies in patients with IBS‐D (n = 1972) . Patients with IBS‐D receiving Tongxie Yaofang were significantly more likely to experience improvement of clinical symptoms vs other treatments (90.3% vs 72.7%, respectively; odds ratio, 4.0; 95% CI, 3.1‐5.3 [ie, pinaverium bromide alone or in combination with a probiotic or montmorillonite powder, glutamine, loperamide, miyarisan, or trimebutine maleate]) . The number needed to treat for Tongxie Yaofang was 5.7 .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with IBS‐D receiving Tongxie Yaofang were significantly more likely to experience improvement of clinical symptoms vs other treatments (90.3% vs 72.7%, respectively; odds ratio, 4.0; 95% CI, 3.1‐5.3 [ie, pinaverium bromide alone or in combination with a probiotic or montmorillonite powder, glutamine, loperamide, miyarisan, or trimebutine maleate]) . The number needed to treat for Tongxie Yaofang was 5.7 . Safety was evaluated in 12 studies included in the meta‐analysis; AEs reported with Tongxie Yaofang included nausea (n = 3 in two studies), compared with 16 AEs reported across the other treatments .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations